Evaluation Of The Effectiveness Of Using The Recommended Method Of Registration Recommendations At Bestari Pusat Kesehatan Masyarakat Medan Petisah - Indri Okta Vielsa Siboro; Chrismis Novalinda Ginting; Sri Lestari Ramadhani; Ulina Karo-Karo (CV. Inara, 2022)
The Suggested Independent Registration (SIR) Method at the Bestari Health Center aims to maximize the outpatient registration process to create an easy, fast and convenient service for patients. However, in its implementation, there are still many elderly people who do notunderstand its use and sometimes there are problems with the system so it slows down the service process at the Bestari Health Center. This study aimed to determine the evaluation of the effectiveness of using the Independent List Recommendation Method at the Bestari Health Center. The method used is Mix Methods, which is a combination of qualitative and quantitative. The population in this study amounted to 105 respondents. Based on the results of research on evaluating the effectiveness of the use of the Suggested Independent Registrationrecommended method at the Bestari Health Center, it can be seen that there is an influence of human resources, SOPs and facilities, and infrastructure on the use of the Suggested Independent Registration method at the Bestari Health Center. The results of interviews with respondents indicate that at Bestari Health Center, there are already human resources to support, SOPs are available but do not work, and infrastructure that already exists but is not functioning properly.